Formative Assessment in EFL Classroom Practices - Widiastuti, Ida Ayu Made Sri; Saukah, Ali (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2017)
This study investigated the challenges and opportunities of formative assessment in EFL classes. It made use of qualitative research design by using indepth interviews to collect the required data. Three teachers and three students were involved as research participants in this study and they were intensively interviewed to get valid and reliable data regarding their understanding of formative assessment and the follow up actions they took after implementing formative assessment. The results of this study showed that the English teachers were found not to take appropriate follow up actions due to their low understanding of formative assessment. The teachers’ understanding could influence their ability in deciding the actions. This study indicates that EFL teachers need urgent further intensive training on the appropriate implementation of formative assessment and how follow up actions should be integrated into classroom practices.